The problem of scope of professionals’ moral responsibility and its applications in legal ethics - Skuczyński, Paweł (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The study concerns a problem of lawyers’ moral responsibility which belongs to the philosophical areas of professional ethics. There are three interpretations of the moral responsibility of lawyers. The simplest of them limits the moral responsibility of the subject to the sphere of duties resulting from social relations connected directly with the subject, in particular professional roles. Hence, in this case we usually speak of the so-called role-responsibility. The second interpretation of the moral responsibility of the subject broadens its scope in comparison to the previous one in that the subject is not only accountable for a sphere of a duty determined by social roles played, but also for the sphere in which their actions may have any sort of influence. In the philosophy of morality this is linked to the question of supererogation. The final concept of a subject’s moral responsibility defines its scope as wide as possible. This means that it encompasses also the sphere in which it does not have any influence. Thus, it may be said that this is responsibility for the present state of the whole world and for this reason it is described as existential responsibility. Additionally, the application of the problem in the fields of legal ethics is discussed, i.e. the issue of “just defences” and the adversary system excuse.